Kajian Wacana Kritis Pada Labelisasi Radikalisme Oleh Agen Badan Nasional Penanggulangan Terorisme - Kholid Kaldun (RETORIKA: Jurnal Ilmu Bahasa, 2016)
Nowadays, radicalism is famous for national and international people around the worl. The development of such issues is adressed from radicalism movement and the way it spreads through social media which is labelled radical by BNPT. This research issues radicalism through the language use for its radicalism aspects that addres the use of radicalism language in social media. Pursuant to factual logical data, views from readers, this research aims at; 1) describing the criteria the language use labelled radical by BNPT in Islamic pages; 2) investigating the ideology of radicalism views in Islamic pages; 3) describing how BNPT views Islamic pages; 4) finding the rellevance result toward the discourse analysis learning in universities. This reseacrh uses critical discourses analysis and descriptive qualitative which is issued from Teun van DijkÂ  critical discourse analysis theory (AWK) and the supporting theory of Halliday, the Raymond William and Louis Althuser theories. The data is obtained through observation and downloaded documentation. The data is analyzed formally and informally, categorized, classified, identified, labelled, and described. The research results that the radical language symbol and criteria, linguistic features, and ideology from the investigated pages are indicated radical whether from the view of BNPT. Analyzing macro and micro aspect, the research reveals that within the investigated texts, it is found that there are three topics of jihad, demonstration, and takfirin. Also there are micro sintactic and semantic aspects, styllistic, and retorical aspects that domain the results. The rellevance of the reserach findings reveals that this research can be used as guidance in analyzing written texts based on critical discourse analysis (AWK) particularly macro and micro analysis.Keywords: Radical, Ideology, Critical Discourse Analysis